2005
DOI: 10.1103/physrevb.71.113403
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy of relative motion of walls in carbon nanotubes

Abstract: We study the interwall interaction and relative motion of walls in carbon nanotubes using density functional theory. The interwall interaction energy surface as a function of relative rotation and sliding of walls is calculated for the ͑5,5͒@͑10,10͒ nanotube. The barriers to relative rotation and sliding are estimated ab initio for the chiral walls of the ͑8,2͒@͑16,4͒ nanotube. These results are used to extract information on experimentally measurable quantities, such as threshold forces, diffusion coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 34 publications
5
56
1
Order By: Relevance
“…As shown in the figure, the interfacial shear strength is independent of the nanotube length. The average shear strength is 30.3 3.2 ± MPa, which matches well with the 26.3 MPa value obtained by Bichoutskaia [2005] for double-walled nanotubes using an ab initio method. Similarly, the interfacial shear strength between a nanotube and epoxy is about 11.2 0.7 ± MPa, as shown in Figure 14.…”
Section: Nanorope-based Composite Modeling and Analysis --Molecular Dsupporting
confidence: 74%
“…As shown in the figure, the interfacial shear strength is independent of the nanotube length. The average shear strength is 30.3 3.2 ± MPa, which matches well with the 26.3 MPa value obtained by Bichoutskaia [2005] for double-walled nanotubes using an ab initio method. Similarly, the interfacial shear strength between a nanotube and epoxy is about 11.2 0.7 ± MPa, as shown in Figure 14.…”
Section: Nanorope-based Composite Modeling and Analysis --Molecular Dsupporting
confidence: 74%
“…59,60,66 It is shown that the calculated potential surfaces of interlayer interaction energy for h-BN layers aligned in the same and opposite directions can be fitted by simple expressions containing only the first components of Fourier expansions determined by symmetry of the layers. Analogous approximations have been suggested previously for graphene bilayer 60,61,66,88 and doublewalled carbon nanotubes 81,[89][90][91][92][93] based both on DFT calculations and semi-empirical potentials. Thus it can be expected that for other layered materials the potential surface of interlayer interaction energy can be also reproduced closely by the first Fourier components determined by symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…We should note that the possibility to accurately approximate potential energy surfaces by expressions containing only the first Fourier harmonics has been previously demonstrated for interaction between graphene layers 60,61,66,88 and between carbon nanotube walls, both for infinite commensurate walls 81,[89][90][91][92] and in the case where corrugations of the potential surface are determined by the contribution of edges 93 or defects. 81 Thus we can expect that analogous expressions can describe potential energy surfaces for other layered materials with the van der Waals interaction between layers or for translational motion of large molecules physically adsorbed on crystal surfaces.…”
Section: Approximation Of Potential Energy Surfacesmentioning
confidence: 99%
“…It imposes in its vicinity AA-stacking, whose energy is only ~7 meV/Å 2 higher than of AB-stacking [13][14][15] . To be concrete, and in accord with typically observed graphene crystallites 16 , we chose exterior shape as hexagon bounded by all-armchair or all-zigzag edges, AGSD or ZGSD.…”
mentioning
confidence: 96%